Can high-flow nasal cannula reduce the risk of bronchopulmonary dysplasia compared with CPAP in preterm infants? A systematic review and meta-analysis - Sabrina de Jesus Brito; Sabrina Pinheiro Tsopanoglou; Endi Lanza Galvão; Franciele Angelo de Deus; Vanessa Pereira de Lima (BMC, 2021)
Abstract Background Bronchopulmonary dysplasia (BPD) is a chronic lung disease that affects the premature lung, and to reduce its incidence has been used non-invasive ventilatory support, such as continuous positive airway (CPAP) and high-flow nasal cannula (HFNC). Thus, the objective of this review was to assess whether the use of high flow nasal cannula (HFNC) compared to continuous positive airway pressure (CPAP) decreases the risk of bronchopulmonary dysplasia (BPD) in premature newborns. Methods The protocol was registered (Prospero: CRD42019136631) and the search was conducted in the MEDLINE, PEDro, Cochrane Library, CINAHL, Embase, and LILACS databases, and in the clinical trials registries, until July 2020. We included randomized clinical trials comparing HFNC versus CPAP use in premature infants born at less than 37 weeks of gestational age. The main outcome measures were the development of BPD, air leak syndrome, and nasal injury. The methodological quality of the included studies was assessed using the Cochrane risk of bias tool and the GRADE system was used to summarize the evidence recommendations. Meta-analyses were performed using software R. Results No difference was found between HFNC or CPAP for the risk of BPD (RR: 1.10; 95% CI: 0.90-1.34), air leak syndrome (RR: 1.06; 95% CI: 0.52-2.14), and nasal trauma (RR: 2.00; 95% CI: 0.64-6.25), with a very low level of evidence. Conclusion(s) The HFNC showed similar results when compared to CPAP in relation to the risk of BPD, air leak syndrome, and nasal injury. In the literature, no randomized clinical trial has been found with BPD as the primary outcome to support possible outcomes.